Pentingnya Imunisasi Sejak Dini, Wujud Cinta Kepada Anak di RW 04 Kelurahan Kertamaya Kota Bogor Tahun 2026 - Fitria Lestari; Shanti Ariandini; Shinta Purnamasuti; Afthalia Oktavisha; Siti Fauziatu; RiniNurfauziah; Nadhita Denia Putri (Lembaga Pengembangan Kinerja Dosen, 2026)
World Health Organization (WHO) reports that immunization is able to prevent approximately 3–5 million deaths each year; however, a number of children still do not receive optimal immunization coverage due to insufficient parental knowledge. This study aimed to analyze the effect of health education on improving mothers’ knowledge regarding early childhood immunization in RW 04, Kertamaya Subdistrict, Bogor City, in 2026. This study employed a pre- experimental design with a one-group pretest–posttest approach involving 30 respondents. Knowledge levels were measured using a questionnaire before and after the health education intervention and analyzed using the Paired Sample T-Test. The results indicated a statistically significant difference in mothers’knowledge levels before and after the health education intervention (p = 0.029). In addition, the proportion of respondents with good knowledge increased from 76.7% in the pre-test to 93.3% in the post-test. These findings demonstrate that health education has a significant effect on improving mothers’ knowledge and can serve as an effective promotive intervention to support the success of community-level immunization programs.